2013
DOI: 10.1038/srep03132
|View full text |Cite
|
Sign up to set email alerts
|

Full Printable Processed Mesoscopic CH3NH3PbI3/TiO2 Heterojunction Solar Cells with Carbon Counter Electrode

Abstract: A mesoscopic methylammonium lead iodide (CH3NH3PbI3) perovskite/TiO2 heterojunction solar cell is developed with low-cost carbon counter electrode (CE) and full printable process. With carbon black/spheroidal graphite CE, this mesoscopic heterojunction solar cell presents high stability and power conversion efficiency of 6.64%, which is higher than that of the flaky graphite based device and comparable to the conventional Au version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
604
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 749 publications
(640 citation statements)
references
References 29 publications
6
604
1
4
Order By: Relevance
“…In fact, similarly to DSCs, it is mainly utilized for the deposition of the nanocrystalline scaffolds in the mesoporous PSC architectures at both the cell level and module level (since it enables patterned deposition of the unit cells 45 ). Arguably one of the most interesting developments regarding screen printing has been the development of fully printed PSCs utilizing a stack of mesoporous layers, 5,46,47 as shown in Figure 3(f). 48 A three-layer stack of 1 µm mesoporous TiO 2 ETL, a 2 µm mesoporous ZrO 2 spacer layer, and a 10 µm mesoporous carbon black/graphite top electrode were all screen printed over a conducting substrate covered by a thin compact layer of TiO 2 .…”
Section: Screen Printingmentioning
confidence: 99%
“…In fact, similarly to DSCs, it is mainly utilized for the deposition of the nanocrystalline scaffolds in the mesoporous PSC architectures at both the cell level and module level (since it enables patterned deposition of the unit cells 45 ). Arguably one of the most interesting developments regarding screen printing has been the development of fully printed PSCs utilizing a stack of mesoporous layers, 5,46,47 as shown in Figure 3(f). 48 A three-layer stack of 1 µm mesoporous TiO 2 ETL, a 2 µm mesoporous ZrO 2 spacer layer, and a 10 µm mesoporous carbon black/graphite top electrode were all screen printed over a conducting substrate covered by a thin compact layer of TiO 2 .…”
Section: Screen Printingmentioning
confidence: 99%
“…19 Previously, we have developed a triple-layer architecture of TiO 2 /ZrO 2 /Carbon to fabricate a hole-conductor-free printable mesoscopic PSC. 21,22 By optimizing the mesoporous scaffold and perovskite absorber, hysteresis-less devices have been obtained with TiO 2 as the electron transporting layer (ETL). 23,24 In this study, it was found that the type of hysteresis effect in printable mesoscopic PSCs was highly dependent on the interlayer of c-TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, perovskite solar cells using poly(triaryl amine) HTLs have achieved the highest certified efficiency 7 . Significant efforts have been paid to search for alternative HBL and HTL materials or even to eliminate HTL layer [11][12][13][14] . Some lead halide perovskite solar cells without HTLs have achieved reasonable conversion efficiencies.…”
mentioning
confidence: 99%